Tietz fundamentals of clinical chemistry and molecular diagnostics - Rifai, Nader; Chiu, Rossa W. K.; Young, Ian (Ian S.); Wittwer, Carl T.
Master clinical lab testing skills with the condensed version of the Tietz Textbook! Designed for use by CLS students, Tietz Fundamentals of Clinical Chemistry and Molecular Diagnostics, 9th Edition provides a streamlined guide to the clinical chemistry knowledge you need to work in a real-world, clinical lab. Coverage ranges from laboratory principles to analytical techniques and instrumentation, analytes, pathophysiology, and more. New content keeps you current with the latest developments in molecular diagnostics. From highly respected clinical chemistry educator Nader Rifai, this textbook shows how to select and perform diagnostic lab tests, and how to accurately evaluate results. Coverage of analytical techniques and instrumentation includes optical techniques, electrochemistry, electrophoresis, chromatography, mass spectrometry, enzymology, immunochemical techniques, microchips, automation, and point of care testing. Authoritative, foundational content mirrors that in the Tietz bible of laboratory medicine but in a more concise way. Updated chapters on molecular diagnostics cover the principles of molecular biology, nucleic acid techniques and applications, and genomes and nucleic acid alterations, reflecting the changes in this rapidly evolving field. Clinical cases from the Coakley Collection demonstrate how concepts from the text are applied in real-life scenarios. More than 400 illustrations and easy-to-read summary tables help you better understand and remember key concepts. Learning objectives, key words with definitions, and review questions are included in each chapter to make learning easier.